La gestión formativa para la investigación en la Universidad Técnica de Cotopaxi carrera de Ingeniería Comercial. Estrategia para el desarrollo de la investigación - Peñaherrera Acurio, Sandra Jaqueline (2015)
The formative management for research in the Cotopaxi Technical University Cotopaxense Alma Mater is the main idea of the research. When the insufficiencies in the research results were detected we analyzed the research process the same one is the object of the research. The diagnostic is synthesized as a scientific problem the insufficiencies in the generation and knowledge development process and the technologic innovation in the Cotopaxi Technical University in relation with the social and scientific process the same ones limit the relevance and impact process by targeting a Formative Management Strategy for the Research being the Formative Management for the Research in the Cotopaxi Technical University the action field. The Formative Management for the Research in the Cotopaxi Technical University is based considering the relation between research formative systematization and the generalization of the new scientific knowledge from the transforming professional practice The Formative Management Strategy for the Research in the Cotopaxi Technical University is the practical contribution. The scientific contribution is the systematization of the Research formation from the transforming professional practice in order to promote the institutional scientific development giving solution to the institutional and social problems from the technical scientific development context.